Analisis bibliometrik pada Pengembangan Desa Wisata - Edouard Aryadi Supriyadi; Luluk Nihayati (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
Studies on the development of tourism villages have been conducted by many researchers in different aspects and locations. This study looks at the development of tourist villages from 2018 to 2022. We used bibliometric analysis by combining two well-known software: Publish and Perish (PoP) and VoS viewer. Data was collected through Google Scholar-based PoP over a 5-year period from 2018 to 2022. The data was generated from Indonesian articles generated from the database using keywords specific to tourism village development. We limited the maximum number of results to 100 articles, then refined by selecting relevant sources and found 70 selected articles. The results showed that existing research on tourism village development on various topics and research networks were visualized. Through collaborative networking, the results can be useful for academic researchers to help them understand the evolution of tourism village development research, identify the underlying themes and assist the development of current tourism village development concepts. This paper is one of the existing papers that provides an understanding of tourism village development as an interesting research topic by examining its development through bibliometric analysis. Based on network visualization with the keyword that appears most often is the development of tourist villages. When viewed from Density Visualization, tourist village, development, village development, village and in the development of tourist villages show that the topic is being the center of research. Then for topics such as community empowerment through tourism villages provides a clue that this study material is still small and very less studied.